2014
DOI: 10.1016/j.cell.2014.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Kingdom Chemical Communication Drives a Heritable, Mutually Beneficial Prion-Based Transformation of Metabolism

Abstract: SUMMARY In experimental science, organisms are usually studied in isolation, but in the wild they compete and cooperate in complex communities. We report a system for cross-kingdom communication by which bacteria heritably transform yeast metabolism. An ancient biological circuit blocks yeast from using other carbon sources in the presence of glucose. [GAR+], a protein-based epigenetic element, allows yeast to circumvent this glucose repression and use multiple carbon sources in the presence of glucose. Some b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(159 citation statements)
references
References 51 publications
1
158
0
Order By: Relevance
“…Also, instead of high-molecular-weight amyloids, LDPrD-GFP formed low-molecular-weight oligomers. We have previously shown that at least one fungal prion, [GAR+], does not form amyloid or require Hsp104; instead, this prion is Hsp70-dependent (36,37). Therefore, it is possible that [LD+] belongs to this noncanonical class of prions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, instead of high-molecular-weight amyloids, LDPrD-GFP formed low-molecular-weight oligomers. We have previously shown that at least one fungal prion, [GAR+], does not form amyloid or require Hsp104; instead, this prion is Hsp70-dependent (36,37). Therefore, it is possible that [LD+] belongs to this noncanonical class of prions.…”
Section: Discussionmentioning
confidence: 99%
“…S3 A-C). Although most known yeast prions are dependent on Hsp104, recently emerging evidence indicates that other molecular chaperones like Hsp70 and, potentially, Hsp90 may play Hsp104-independent roles in prion biology (9,36,37 (Fig. 4A).…”
Section: Identification and Functional Classification Of Arabidopsis mentioning
confidence: 99%
“…Waddington stressed the importance of cytoplasmic compounds and their effect on gene expression (Waddington 1935), yet maternal or transgenerational effects mediated by cytoplasmic transfer from mother to offspring would not be considered epigenetic under Holliday's definition because the expression pattern of the offspring is not independent and simply results from the transfer of cytoplasmic compounds, such as RNA, transcription factors, prions, etc. (Ptashne 2008;Jarosz et al 2014). These issues make the contrast between Waddington's epigenetics and Holliday's epigenetics much more evident.…”
Section: Heritabilitymentioning
confidence: 99%
“…One important goal within these efforts is to understand how microbes interact with each other and the consequences of such interactions at the level of their transcriptomes, proteomes, and metabolomes. For instance, it has been demonstrated that the metabolism of yeast can be transformed by bacteria-induced prions to decrease the release of inhibiting ethanol (7). In another study, an oral biofilm of the genus Streptococcus displayed different transcriptional responses toward the presence of other species in mixed-species cultures (8).…”
mentioning
confidence: 99%